The gains from trade in an specific factor growth model - Fischer, Ronald; Serra, Pablo (Estudios de Economía, 2016)
This paper uses a dynamic model of trade with specific factors of production to analyze the evolution of an economy that opens to international trade. Each period the allocation of labor is determines by previous period investment. The model cannot adapt instantaneously to free trade conditions, even though they improve welfare. Transition to the free trade steady state is costly and, among all feasible trajectories, those that have the longest adjustment paths are optimal. In fact, fast transitions can lead to losses from trade. On the other hand, if autarkic prices are very different from world prices, fast adjustment is preferable, since adjustment costs can be compensated by the large gains from specialization under trade.